2010
DOI: 10.7589/0090-3558-46.4.1141
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Free-Ranging Endangered European Mink (Mustela Lutreola) and Other Small Carnivores (Mustelidae, Viverridae) From Southwestern France

Abstract: ABSTRACT:To study the possible role of disease in the decline of endangered European mink (Mustela lutreola), we conducted a survey of antibody prevalence and renal carriage of pathogenic leptospira (Leptospira interrogans sensu lato) using serum and kidney samples collected from 1990 to 2007 from several free-ranging small carnivores and farmed American mink (Mustela vison) in southwestern France. An indirect microscopic agglutination test using a panel of 16 serovars belonging to 6 serogroups (Australis, Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
2
20
0
3
Order By: Relevance
“…An MST database was created from spacer sequences obtained for Leptospira sp. strains belonging to the Icterohaemorrhagiae, Australis, Grippotyphosa, and Canicola serogroups (Table 2), which are highly prevalent in France, with the seroprevalence of the Icterohaemorrhagiae serogroup in rodents being as high as 45.6% (12,(27)(28)(29)(30). The choice of spacer was based on the same MLST scheme (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An MST database was created from spacer sequences obtained for Leptospira sp. strains belonging to the Icterohaemorrhagiae, Australis, Grippotyphosa, and Canicola serogroups (Table 2), which are highly prevalent in France, with the seroprevalence of the Icterohaemorrhagiae serogroup in rodents being as high as 45.6% (12,(27)(28)(29)(30). The choice of spacer was based on the same MLST scheme (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MST permitted the phylogeographical lineages to be defined (26), which is of great interest in epidemiologic studies. In this study, we investigated the MST for L. interrogans species genotyping, particularly for the Icterohaemorrhagiae, Canicola, Australis, and Grippotyphosa serogroups, which are the most prevalent serogroups in France (12,(27)(28)(29)(30). The results of MST genotyping have been subsequently compared with the results of the VNTR analysis used as the reference molecular typing method.…”
mentioning
confidence: 99%
“…Over two centuries of research has reported on nematodes isolated from a very wide range of viverrid species (Table 5). While many were not identified to species level, nematodes (Smith et al, 1961;Tsai et al, 1973;Mill an et al, 2009;Moinet et al, 2010) Family Bartonellaceae Bartonella henselae…”
Section: Common Genetmentioning
confidence: 99%
“…Importantly, we identified a higher prevalence (55.6%, with 95% confidence interval = 24, 8-86, 4) compared with previous reports of 23.5% of Leptospira in wild animals in Spain (Millán et al, 2009), which used the MAT to detect the presence of Leptospira. Another study reported by Moinet et al (2010) identified a prevalence of 86% in wild American mink in France MAT detection. The same study detected by PCR a renal carriage of 26% on free-ranging American minks.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Leptospira transmission is very complex, in fact, this is a pathogen of multiple hosts, which often resides in one or more epidemiologically connected populations (Haydon et al 2012). The complexity of Leptospira transmission along with the abundance of mink populations indicates that minks may be an important link in the ecology of leptospires, especially due to their wide distributions, semiaquatic live, and diet (Medina 1997;Millán et al 2009;Moinet et al 2010;Sepúlveda et al 2011). In this study, we determined and characterized the presence of pathogenic Leptospira species in North American minks in Southern Chile.…”
Section: Introductionmentioning
confidence: 99%